2007
DOI: 10.1038/ncb1663
|View full text |Cite
|
Sign up to set email alerts
|

Ring1-mediated ubiquitination of H2A restrains poised RNA polymerase II at bivalent genes in mouse ES cells

Abstract: Changes in phosphorylation of the carboxy-terminal domain (CTD) of RNA polymerase II (RNAP) are associated with transcription initiation, elongation and termination. Sites of active transcription are generally characterized by hyperphosphorylated RNAP, particularly at Ser 2 residues, whereas inactive or poised genes may lack RNAP or may bind Ser 5-phosphorylated RNAP at promoter proximal regions. Recent studies have demonstrated that silent developmental regulator genes have an unusual histone modification pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
606
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(647 citation statements)
references
References 30 publications
36
606
0
3
Order By: Relevance
“…Bivalent domains marked by both H3K4me3 and H3K27me3 are a reported hallmark of the chromatin state of mammalian ES cells (Azuara et al 2006;Bernstein et al 2006). It has been proposed that bivalently marked genes are resolved upon differentiation (Bernstein et al 2006;Stock et al 2007;Landeira et al 2010). However, in X. tropicalis embryos, H3K27me3 deposition follows H3K4me3 deposition in time and is linked to spatial restriction of gene expression (Akkers et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Bivalent domains marked by both H3K4me3 and H3K27me3 are a reported hallmark of the chromatin state of mammalian ES cells (Azuara et al 2006;Bernstein et al 2006). It has been proposed that bivalently marked genes are resolved upon differentiation (Bernstein et al 2006;Stock et al 2007;Landeira et al 2010). However, in X. tropicalis embryos, H3K27me3 deposition follows H3K4me3 deposition in time and is linked to spatial restriction of gene expression (Akkers et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found evidence for poised polymerase at a panel of bivalent gene promoters in ES cells [32].…”
Section: Role Of Bivalent Domains In Differentiated Cellsmentioning
confidence: 99%
“…In particular, the initiation form of RNAPII is phosphorylated at serine 5 (RNAPII-S5p), whereas the elongating form of the enzyme is phosphorylated at serine 2 (RNAPII-S2p). Because RNAPII-S5p has recently been shown to be often associated with genes that are on the point of being, but are not yet, transcribed (Stock et al, 2007;Core and Lis, 2008;Ferrai, unpublished data), we used antibodies that recognize RNAPII-S2p as a mark of active transcription. As shown in Figure 6, in the absence of RA, when HoxB2 is not transcribed, none of the antibodies immunoprecipitated the HoxB2 enhancer.…”
Section: Ra Recruits Prep1 Rnapii the Actin-polymerization Machinermentioning
confidence: 99%